Technology Adoption Intention Among Tinapa Producers in Rosario, Cavite, Philippines: A Correlational and Narrative Analysis - Xavier Lawrence Mendoza; Nerisa B Abug; Sally A Roguel (Inclusive Society and Sustainability Studies, 2025)
Rosario, Cavite, Philippines, well-known for its tinapa production, exemplifies the importance of the artisanal food production sector, where the traditional practice of tinapa making is deeply embedded in the local economy and culture. This sector often relies on manual processes that could benefit from technological innovation to enhance efficiency and product quality. Recognizing this potential, this study investigates the factors influencing technology adoption intention among tinapa producers in Rosario, Cavite, Philippines, employing a descriptive-correlational and narrative research design. Quantitative data from 40 tinapa producers were collected using survey questionnaires, while qualitative insights were gathered through semi-structured interviews. The results indicate that the respondents have a neutral intention towards technology adoption. Correlation analysis reveals that technology adoption intention is significantly and positively related to perceived benefits, technological know-how, and available resources. In contrast, perceived risk did not significantly influence adoption intention. The narrative analysis highlights that producers' inclination towards technology adoption is constrained by strong adherence to traditional practices, limited technological awareness, and resource scarcity, despite recognizing potential modernization advantages. The study concludes that effective technology adoption strategies must integrate financial support, infrastructure development, and tailored education to address the unique challenges and cultural context of tinapa producers.